Platelets as Mediators of Thromboinflammation in Chronic Myeloproliferative Neoplasms - Marin Oyarzún, Cecilia P.; Heller, Paula G. (Frontiers in Immunology, 2019)
Chronic myeloproliferative neoplasms (MPN) are stem cell disorders driven by mutations in JAK2, CALR or MPL genes and characterized by myeloid proliferation and increased blood cell counts. They encompass three closely related conditions, including essential thrombocythemia, polycythemia vera and primary myelofibrosis. Elevated levels of cytokines released by clonal and non-clonal cells generate a chronic proinflammatory state that contributes to disease pathogenesis. Thrombosis represents the most common cause of morbidity and mortality in MPN, although paradoxically, patients may also present with a bleeding diathesis. The mechanisms leading to thrombosis are complex and multiple and include increased blood cells together with qualitative abnormalities of red cells, leukocytes and platelets that favour a prothrombotic activated phenotype. The functional interplay between blood cells, the clotting cascade and dysfunctional endothelium contributes to hypercoagulability and this process is perpetuated by the effect of inflammatory cytokines. In addition to their well-known function in hemostasis, platelets contribute to innate immunity and inflammation and play a key role in MPN thromboinflammatory state. In vivo platelet activation leads to platelet aggregate formation and exposure of adhesion molecules which favour their interaction with activated neutrophils and monocytes leading to circulating platelet-leukocyte heterotypic aggregates. Platelets are recruited to the activated endothelium further enhancing the reciprocal activation of both cell types. Crosstalk between activated cells drives cytokine production, further fuelling the self-reinforcing thromboinflammatory loop. In addition, MPN platelets provide a procoagulant scaffold which triggers the coagulation cascade and platelet-derived microparticles amplify this response. Markers of platelet, leukocyte, endothelial and coagulation activation are increased in MPN patients although prospective studies are required to determine the potential value of these parameters for identifying patients at increased thrombotic risk. Thrombosis remains the main complication of MPN patients, with a high risk of recurrence despite adequate cytoreductive and antithrombotic treatment. Deeper insight into the mechanism favouring thrombosis development in this setting may lead to novel therapeutic approaches for MPN thrombosis. Considering the critical role of inflammation in the vascular risk, concomitant targeting of inflammatory pathways could potentially impact on primary or secondary prevention strategies.